1986
DOI: 10.1203/00006450-198601000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Linoleic Acid Deficiency in Cystic Fibrosis

Abstract: ABSTRACT. To identify evidence of essential fatty acid deficiency, we screened 64 patients with cystic fibrosis by analyzing total lipid extracts from plasma. Forty-three had an abnormal linoleate (18:2) level (less than 26%). Thirteen deficient patients (aged 10-24 yr) ingested for 1 yr 7% of their total calories as linoleate derived from a daily supplement of Microlipid. Five deficient patients (aged 10-37 yr) served as controls. Plasma and erythrocyte fatty acid composition were monitored by gas chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 25 publications
2
33
1
Order By: Relevance
“…19 Another study by van Egmond et al 25 showed better growth among infants who had CF and consumed a predigested formula that contained high LA (12% of energy) compared with those who consumed a comparable formula with lower LA (7% of energy), despite a lower intake of total energy in the former group. In support of these findings, studies of oral supplementation by Mischler et al 24 In view of the findings described above, we hypothesized that sustained high energy intake (1EN) and normal plasma essential fatty acid status are critical determinants of treatment responsiveness. Data from children who have CF and are enrolled in the Wisconsin CF Neonatal Screening Project 20,27 were used to examine this hypothesis for the period of 2 years after CF diagnosis.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…19 Another study by van Egmond et al 25 showed better growth among infants who had CF and consumed a predigested formula that contained high LA (12% of energy) compared with those who consumed a comparable formula with lower LA (7% of energy), despite a lower intake of total energy in the former group. In support of these findings, studies of oral supplementation by Mischler et al 24 In view of the findings described above, we hypothesized that sustained high energy intake (1EN) and normal plasma essential fatty acid status are critical determinants of treatment responsiveness. Data from children who have CF and are enrolled in the Wisconsin CF Neonatal Screening Project 20,27 were used to examine this hypothesis for the period of 2 years after CF diagnosis.…”
Section: Methodsmentioning
confidence: 75%
“…23 In addition to optimizing energy intake, normalizing plasma essential fatty acid status was reported to be associated with better growth in children with CF. 19,[24][25][26] Low plasma linoleic acid (LA) concentrations and essential fatty acid deficiency are evident even among infants whose CF is diagnosed before 6 weeks of age via neonatal screening, with 54% having low plasma LA and 27% having abnormal triene/tetraene ratio. 18 Plasma LA concentration was shown to be correlated positively with growth in children whose CF was diagnosed before 3 months and followed up to 12 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…Results were variable but most showed minimal (7,35) or no (36) improvement in EFA status; however, caloric intakes, when reported, were below the RDA for control subjects (7). Improvements of plasma linoleic acid was observed in CF patients when dietary supplementation was directed at increasing calories as well as linoleic acid (9,37). We attribute the improvement in the EFA status of our CF patients to an improved caloric intake in the Dresence of a linoleic acid intake in excess of the RDA of 3% of total calories.…”
Section: Discussionmentioning
confidence: 99%
“…Many abnormalities were subsequently discovered [4,5] and different oral [6,7] or parenteral [8,9] lipid supplements were administered to CF subjects in order to correct the defects [10,11]. Early studies attributed these abnormalities only to fat malabsorption; afterwards, the existence of an association between the basic defect and abnormal metabolism of essential fatty acids in CF was hypothesized [4,12].…”
Section: Introductionmentioning
confidence: 99%